IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA BERENCANA DI PUSKESMAS KEDUNGDORO KECAMATAN TEGALSARI KOTA SURABAYA - Anisa Kurniatul Azizah; Fatimatul Mukhibbah Azkiya; Anidya Pryhasstya Puteri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
This study aims to determine the process of implementing the KB Village program. In this study, the focus will be on what factors determine the process of implementing the KB village program. Broadly speaking, the KB Village program is an attempt by the central government through the BKKBN to move people to live a more prosperous and quality life. This study aims to describe the implementation of the KB Village program in Tegalsari District. This research method is descriptive using a qualitative approach. The population in this study was taken from 3 locations in the KB Village in Tegalsari District, Surabaya City. For the purposes of this research related to the establishment of Family Planning Counseling in Tegalsari District, the research was focused on KB Village, Tegalsari Sub-District (Malang Village), Dr. Sutomo (Pandegiling), Wonorejo Village. The results showed that the implementation of the KB Village program in Tegalsari District had gone well in terms of planning, coordination with the Kedungdoro Health Center in Surabaya, availability of infrastructure, contraceptives, and supervision. In addition, obstacles that need to be addressed are funding and PLKB personnel in the field. Therefore the implementation of the KB village program in Tegalsari District needs to be improved in the future. Keywords: Implementation, family planning, health center